Postsynthesis Potassium‐Modification Method to Improve Stability of CsPbBr3 Perovskite Nanocrystals. Issue 6 (16th February 2018) - Huang, Shouqiang; Wang, Bo; Zhang, Qi; Li, Zhichun; Shan, Aidang; Li, Liang
Abstract: In this communication, a simple postmodification method to improve the optical properties and stability of CsPbBr3 perovskite nanocrystals (CPB‐NCs) is reported. By strictly controlling the adding dose of K‐oleate (molar ratio of K/Cs = 1.5/1) into the parent CPB‐NC solution, it is possible to synthesize monodispersed K‐modified CPB‐NCs (K‐CPB‐NCs) with drastically enhanced photo‐ and thermostabilities as well as photoluminescence quantum yields, which are increased to 83% from 65%. Photostability tests show that the parent CPB‐NC film drops to 50% of its original PL intensity after 45 h of illumination, but the K‐CPB‐NC film can maintain 100% of PL even after 153 h. Through the morphology, structure, and composition evolution of K‐CPB‐NCs, these benefits were attributed to the modification of K + ions, which possibly induces a strong K‐related protective passivation layer on the surface of K‐CPB‐NCs and simultaneously drastically decreases their surface defects. Abstract : Postmodification of CsPbBr3 nanocrystals (CPB‐NCs) with monovalent cations of K + is investigated by introducing K‐oleate into their colloidal solution, and the K‐modified CPB‐NCs (K‐CPB‐NCs) with surface passivation effects are synthesized. In comparison to the parent CPB‐NCs, K‐CPB‐NCs possess much improved photoluminescence quantum yields (>80%) and stability.